Intrathecal baclofen for neuropathic pain in spinal cord injury: A systematic review - Wibowo, Riky Novriansyah; Subagio, Eko Agus; Faris, Muhammad; Fahmi, Achmad; Turchan, Agus; Utomo, Budi (Edelweiss Applied Science and Technology, 2026)
Neuropathic pain is a debilitating spinal cord injury (SCI) complication often resistant to conventional treatments. Intrathecal baclofen, a γ-aminobutyric acid type B (GABAB) receptor agonist, has been suggested to provide additional analgesic benefits. This systematic review evaluated the efficacy and safety of intrathecal baclofen for neuropathic pain in patients with SCI, as well as its effects on spasticity and quality of life. Following PRISMA 2020 guidelines, we searched major databases through January 2024 for trials and cohort studies of intrathecal baclofen in adults with SCI. Risk of bias was assessed using RoB 2 and ROBINS-I tools. A narrative synthesis was performed due to substantial study heterogeneity. Among 48 patients across four studies, three reported meaningful reductions in neuropathic pain following intrathecal baclofen, as reflected in validated pain scales such as the Numerical Rating Scale, Neuropathic Pain Symptom Inventory, Brief Pain Inventory, and Visual Analogue Scale. Greater improvements were observed in paroxysmal pain and dysesthesia than in continuous pain or allodynia. All studies reported significant reductions in spasticity, primarily assessed using the Modified Ashworth Scale. Functional outcomes and quality-of-life domains improved where reported. Adverse events were generally mild and transient, with no serious complications. Intrathecal baclofen is a promising adjuvant for SCI-related neuropathic pain, providing consistent benefits for spasticity and quality of life. However, limited evidence from small, heterogeneous studies necessitates larger, well-designed randomized controlled trials to confirm these findings.